Correlation between SARS‐COV‐2 antibody screening by immunoassay and neutralizing antibody testing. Issue 4 (25th January 2021) - Mendrone‐Junior, Alfredo; Dinardo, Carla Luana; Ferreira, Suzete Cleuza; Nishya, Anna; Salles, Nanci Alves; de Almeida Neto, Cesar; Hamasaki, Debora Toshei; Facincani, Tila; de Oliveira Alves, Lucas Bassolli; Machado, Rafael Rahal Guaragna; Araujo, Danielle Bastos; Durigon, Edison Luiz; et al.
Abstract: Background: The efficacy of convalescent plasma (CP), an alternative for the treatment of COVID‐19, depends on high titers of neutralizing antibodies (nAbs), but assays for quantifying nAbs are not widely available. Our goal was to develop a strategy to predict high titers of nAbs based on the results of anti‐SARS‐CoV‐2 immunoassays and the clinical characteristics of CP donors. Study Design and Methods: A total of 214 CP donors were enrolled and tested for the presence of anti‐SARS‐CoV‐2 antibodies (IgG) using two commercial immunoassays: EUROIMMUN (ELISA) and Abbott (Chemiluminescence). Quantification of nAbs was performed using the Cytopathic Effect‐based Virus Neutralization test. Three criteria for identifying donors with nAbs ≥ 1:160 were tested: – C1: Curve ROC; − C2: Conditional decision tree considering only the IA results and – C3: Conditional decision tree including both the IA results and the clinical variables. Results: The performance of the immunoassays was similar referring to both S/CO and predictive value for identifying nAbs titers ≥1:160. Regarding the studied criteria for identifying CP donors with high nAbs titers: (a) C1 showed 76.1% accuracy if S/CO = 4.65, (b) C2 presented 76.1% accuracy if S/CO ≥4.57 and (c) C3 had 71.6% accuracy if S/CO was ≥4.57 or if S/CO was between 2.68‐4.57 and the last COVID‐19‐related symptoms were recent (within 19 days). Conclusion: SARS‐CoV‐2 IgG immunoassays (S/CO) can be used to predict high anti‐SARS‐CoV‐2 nAbs titers. This study has proposed different criteria for identifying donors with ≥1:160 nAbs titers, all with high efficacy.